Epipsammic diatom fauna of Karabey Creek in Türkiye - Caglar, M.; Bulut, H.; Selamoglu, Z. (Green Wave Publishing of Canada, 2022)
This researching includes investigations of monthly changes in the population size and density of the diatoms in the Epipsammic samples taken from Karabey Creek in Bingöl, Türkiye between March-November 2020. Throughout the research, 31 taxa belonging to Bacillariophyta was recorded in the first station and 37 taxa were recorded in the second station. Navicula and Nitzschia was the diatom species that were represented by 5 taxa, the highest number in the first station, in the second station, Cymbella, Navicula and Nitzschia were the diatom species that were represented by the most taxa with 5 taxa. In March, the first station’s highest relative density (10.63%) belonged to Ulnaria ulna species while the lowest density (0.73%) belonged to Encyonema ventricosum, Fragilaria tenera and Surirella minuta species in May. In the second station, the highest relative density (8.73%) belonged to Ulnaria ulna species in March while the lowest density (1.09%) belonged to Pinnularia nobilis, Surirella ovalis and Encyonema elginense species in April. Measurements concerning temperature, dissolved oxygen and pH were also conducted for the water samples taken from the stations. The measured variables are found to be positive for the development of diatoms in epiliton. Relative density of the diatoms found in the Epipsammic flora was recorded. © 2022, Green Wave Publishing of Canada. All rights reserved.
Keywords: Diatom; Epipsammic; Karabey Creek